APPLICATIONS OF FUZZY LOGIC, SENSING, AND IOT TECHNOLOGIES IN THE MONITORING OF ENVIRONMENTAL CONDITIONS IN LAYER POULTRY HOUSES: A SCOPING REVIEW - de Albuquerque, Leandro Calixto Tenório; Leite, Alisson Rodolfo; Gabriel Filho, Luís Roberto Almeida; Gabriel, Camila Pires Cremasco (Seven Editora, 2025)
Given the relevance of layer poultry farming to Brazilian agribusiness and the need to ensure adequate environmental conditions for bird welfare and productive performance, it is pertinent to investigate how technologies and intelligent models have been applied to the housing environment of poultry facilities. This study aims to identify, map, and characterize research that integrates, individually or in combination, fuzzy logic, environmental sensing, and IoT technologies in the monitoring of the environment in layer poultry houses. A scoping review was conducted according to JBI methodology and PRISMA-ScR guidelines, including database searches, rigorous study selection, and data extraction. A total of 52 studies published between 2020 and 2025 were included. Most research was carried out in Indonesia and China, with a predominance of field studies. Temperature and humidity were the most frequently monitored variables, whereas gas measurements appeared less frequently. Low-cost sensors from the DHT and MQ families and hardware platforms such as ESP and Arduino were predominantly employed. Fuzzy logic was the main artificial intelligence technique identified, although many systems operated without intelligent models. Most proposals were integrated with cloud-based solutions, but few employed long-range wireless networks. The review also identified many studies focused on broiler chickens, limited adoption of environmental classification, and an almost complete absence of validation using recognized environmental indices. It is concluded that, despite the technological advances observed, important gaps remain regarding environmental classification and validation, the use of artificial intelligence, gas monitoring, long-range communication, and the development of solutions specifically tailored to layer poultry houses. DOI: https://doi.org/10.56238/sevened2025.036-136